SPECIAL issue on changes and trends in public administration (1994)
"This issue presents the data on shifts in the role and scope of government, administrative restructuring and reforms and modernization of administrative functions of seven governments in the Asian Pacific Region: Australia, India, Indonesia, Korea, Malaysia, the Philippines, and Thailand. The various studies encompass contextual factors which are affecting the performance of public administration system such as globalization of economics, privatization of public enterprises, emphasis on environment concern and mandates for popular participation. The studies also hope to provide information on innovative responses of governments to these contextual trends, especially shifts in the role and scope of government
Keywords: Public Administration